MENGANALISIS EFEKTIVITAS EWOM PADA CUSTOMER PURCHASE INTENTION DENGAN MENGGUNAKAN SOCIAL NETWORKING OF SMARTPHONE IN BATAM - Golan Hasan; Dennis Lim (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
Social Networking is used by a lot people in this world so they still can connected with their families, friend and customer. Some people used to tell their families or friend what’s their dailies do by putting a picture selfie. The most important part where there’s a people use Social Networking as business purpose like make adversiting for their business without use any capital.The purpose of the study was investigated how far the effect of electric Word Of Mouth (eWOM) inside social networking sites (facebook) on consumer purchase intention through mobile phone.This study produced existing literature of electric Word of Mouth, Value co-creation, and customer behavior in social networking sites and with our search will help marketers to develop a new ways to share their product information on networking sites.